Pentingnya pendidikan Pancasila dan karakter untuk menumbuhkan sikap bela negara dalam diri mahasiswa - Permata, Divia Atma (Maliki Interdisciplinary Journal, 2023)
To instill a sense of nationalism in students, the education system must incorporate Pancasila and character education. Education that prioritizes character and Pancasila also fosters a pro-environmental attitude and increases understanding of sustainability, produces graduates who have strong morals and have a positive outlook on change. To do this, educational institutions must provide a comprehensive and integrated curriculum that actively engages students in developing a sense of ownership, collaboration and responsibility. In conclusion, Pancasila and character education is very important to instill a sense of nationalism in students and prepare them to lead the next generation.